(untitled) (Bangladesh Pharmaceutical Journal, 2018)
The present study was designed to evaluate the anti-nociceptive and anti-inflammatory properties of the ethanolic extract of Crotalaria pallida Aiton (Family: Fabaceae) leaves based on its traditional uses in the treatment of urinary disorders, external application as a poultice to treat painful swelling of joints and to reduce fever. The anti-nociceptive effect was assessed in mice using acetic acidinduced writhing, formalin-induced paw licking and tail immersion assays. Anti-inflammatory activity was evaluated by carrageenan induced paw oedema in rats. In acetic acid-induced writhing test, the extract at different doses (50 mg/kg and 100 mg/kg bw) significantly (p<0.001) and dose-dependently reduced pain by 37.50% and 47.70%, respectively. The extract also significantly inhibited formalininduced paw licking in mice at both the early and late phases. In the tail immersion test, the extract caused a significant inhibition of pain (64.91% inhibition after 4 hrs) at a dose of 100 mg/kg. C. pallida exhibited a considerable inhibition of paw oedema development in the carrageenan-induced oedema test. The findings of the study suggested that C. pallida leaves have significant anti-nociceptive and antiinflammatory effects, confirming the traditional uses of this plant in the treatment of various diseases associated with pain and inflammation. Bangladesh Pharmaceutical Journal 20(2): 165-171, 2017